Synthesis and Characterization of Novel Tetradentate ligand Type N4 and its Complexes With CoII,NiII,and PdII. - Yousif, E. I. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
A new Schiff base ligand [2,3,8,9–tetra -phenyl-1,4,5,7,10,12-hexa azo-5,12- dihydro -6,11- dione 1,3,7,10-dudec-tetra-ene] [H2L] and its complexes In general formula [M(H2L)]Cl2 (where : M= CoII, NiII, and PdII) were prepared. This ligand was prepared in two steps,in the first step a solution of benzil in methanol was reacted under reflux with semicarbazidhydrochlorid to give an (intermediate compound)[benzyl bis–(Semicarbazone)] which was reacted in the second step with benzil giving the mentioned ligand. The complexes CoII, NiII, and PdII were synthesized by direct reaction of the corresponding metal chloride with the ligand [H2L].The ligand and complexes were characterized by spectroscopic methods (IR, UV-Vis, and atomic absorption), chloride content and conductivity measurement.From the data of these measurements, we suggestred a tetrahedral geometry for CoII, NiII complexs and a square planar for PdII complex.